Case Report: Next-Generation Sequencing-Based Detection in A Patient with Three Synchronous Primary Tumors - Wu, Tianqi; Wan, Jian; Xia, Kai; Yang, Muqing; Feng, Lijin; Yin, Lu; Chen, Chunqiu (Frontiers in Oncology, 2022)
Multiple primary tumors (MPTs) are defined as growth or development of two or more neoplasms in the same individual and clinically rare. We admitted a case of a 57-year-old female who developed 2 primary cancers (breast cancer and gastric cancer) and a GIST. Next-generation sequencing (NGS) of the 3 tumors and of blood was performed to determine the clonal origin and identify genetic cancer susceptibility. NGS allowed the identification of germline genetic variants potentially correlated with an individual risk of developing multiple cancers and different additional mutations required to drive the formation of different tumors.